ISSUES IN THE DEVELOPMENT OF FRILANCE ACTIVITIES IN THE CONTEXT OF THE DEVELOPMENT OF THE DIGITAL ECONOMY - Tursunalievich, Abdulhakimov Zuhrali (The journal of contemporary issues in business and government, 2021)
In the article, in the context of the ongoing COVID-19 pandemic in the world economy, each country is developing ways to ensure sustainable economic development and existing employment. The goal is to develop freelance activities in the economy by paving the way for digital technologies and platforms.